Insulin/IGF-I and Related Signaling Pathways Regulate Aging in Nondividing Cells: from Yeast to the Mammalian Brain - Edoardo Parrella; Valter D. Longo (The Scientific World Journal)
Mutations that reduce glucose or insulin/insulin-like growth factor-I (IGF-I) signaling increase longevity in organisms ranging from yeast to mammals. Over the past 10 years, several studies confirmed this conserved molecular strategy of longevity regulation, and many more have been added to the complex mosaic that links stress resistance and aging. In this review, we will analyze the similarities that have emerged over the last decade between longevity regulatory pathways in organisms ranging from yeast, nematodes, and fruit flies to mice. We will focus on the role of yeast signal transduction proteins Ras, Tor, Sch9, Sir2, their homologs in higher organisms, and their association to oxidative stress and protective systems. We will discuss how the “molecular strategy” responsible for life span extension in response to dietary and genetic manipulations appears to be remarkably conserved in various organisms and cells, including neuronal cells in different organisms. Taken together, these studies indicate that simple model systems will contribute to our comprehension of aging of the mammalian nervous system and will stimulate novel neurotherapeutic strategies in humans.